Kandungan Gizi dan Profil Asam Amino Tepung Ikan Sepat Siam (Trichigaster pectoralis) - Wahyu Perdana Putra; Rodiana Nopianti; Herpandi Herpandi (Jurnal FishtecH, 2017)
The purposes of this research were to investigate the nutritional content and profile amino acid of siamese gourami (Trichogaster pectoralis) fish meal. This research was conducted on Agustus 2016 until Oktober 2016. This research method used laboratory experiments and the result then analyzed descriptively. Parameters observed were proximate analysis consisting of moisture content, ash content, fat content and protein content, amino acid analysis and the analysis mineral of calcium and phosphorus. The result showed that water content, protein content, fat content, the ash content of siamese gourami for fish meal material were 79.27%, 5.08%, 3.50% and 3.16% respectively. While water content, protein content, fat content, the ash content of siamese gourami fish meal were 2.68%, 65.21%, 4.22%, 18.65% respectively. According to amino acid analysis, on siamese gourami for the material fish meal had detected 18 amino acid was detected that consist of 10 essential amino acid with the total value 69,437.92 mg/kg and 8 non-essential amino acid with the total value 68,448.62 mg/kg. While for siamese gourami fish meal had detected 18 amino acid that consists of 10 essential amino acid with the total value 366,629.6 mg/kg and 8 non-essential amino acid with the total value 381,846.88 mg/kg. The value for calsium and phosphorus siamese gourami (Trichogaster pectoralis) were 0.0034% and 0.1964% respectively. While the value for calcium and phosphorus of fish meal were 0.004% and 0.26% respectively and the whiteness value was 55.44%.